Mandibular morphology and the Mesolithic–Neolithic transition in Westernmost Iberia - Ricardo Miguel Godinho; Cláudia Umbelino; António Carlos Valera; António Faustino Carvalho; Nuno Bicho; João Cascalheira; Célia Gonçalves; Patricia Smith (Scientific Reports, 2023)
Abstract Neolithic farming and animal husbandry were first developed in the Near East ~ 10,000 BCE and expanded westwards, reaching westernmost Iberia no later than 5500 BCE. It resulted in major social, cultural, economic and dietary changes. Yet, the impact of this change on human mandibular morphology in Iberia is yet to be assessed, which is regrettable because mandible form is impacted by population history and diet. In this study we used Mesolithic to Chalcolithic Iberian samples to examine the impact of this transition on mandibular morphology. We also compared these samples with a Southern Levantine Chalcolithic population to assess their relationship. Lastly, we assessed dental wear to determine if the morphological differences identified were related to the material properties of the diet. We found differences between samples in mandibular shape but not size, which we attribute to contrasting population histories between Mesolithic and later populations. Some differences in the severity of dental wear were also found between Mesolithic and later Iberian samples, and smaller between the Mesolithic Iberians and southern Levantines. Little relationship was found between wear magnitude and mandibular shape. Altogether, our results show that the Mesolithic–Neolithic Iberian transition resulted in a meaningful change in mandibular morphology, which was likely driven more by population history than by dietary change.